2018
DOI: 10.1111/aogs.13286
|View full text |Cite
|
Sign up to set email alerts
|

Waterbirth in Sweden – a comparative study

Abstract: In this low-risk population, waterbirth is associated with positive effects on perineal tears, the frequency of interventions, the duration of labor and women's birth experience. Midwives handling waterbirth should be aware of the risk of umbilical cord avulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 23 publications
0
35
0
14
Order By: Relevance
“…According to literature, waterbirth is safe for women with healthy pregnancies and low‐risk births (Davies et al, 2015; Nutter et al, 2014; Taylor et al, 2016; Ulfsdottir, Saltvedt, & Georgsson, 2018; Vanderlaan et al, 2018) and should thus be presented as an alternative for pregnant women who consider ways to give birth. Our findings illustrate that while women appreciate the opportunity to give birth in water, a positive birthing experience can be hampered if the equipment is unsuitable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature, waterbirth is safe for women with healthy pregnancies and low‐risk births (Davies et al, 2015; Nutter et al, 2014; Taylor et al, 2016; Ulfsdottir, Saltvedt, & Georgsson, 2018; Vanderlaan et al, 2018) and should thus be presented as an alternative for pregnant women who consider ways to give birth. Our findings illustrate that while women appreciate the opportunity to give birth in water, a positive birthing experience can be hampered if the equipment is unsuitable.…”
Section: Discussionmentioning
confidence: 99%
“…While studies investigating prevalence of waterbirth is scarce, the literature suggest that it occurs on all continents and possibly is more common in high‐income countries (Garland, 2010). Research has not identified any increase in maternal mortality or morbidity for women who give birth in water with healthy full‐term pregnancies and low‐risk births in cephalic presentation (Nutter, Meyer, Shaw‐Battista, & Marowitz, 2014; Ulfsdottir, Saltvedt, & Georgsson, 2018). No differences has been observed in low risk births between children born in and out of water with regard to neonatal outcomes, including Apgar scores, postnatal infections, umbilical cord samples, and admissions to neonatal intensive care (Davies, Davis, Pearce, & Wong, 2015; Taylor et al, 2016; Vanderlaan, Hall, & Lewitt, 2018), indicating that waterbirth is a safe alternative for many women.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that since those women were focused on natural birth assistance, many of the women may not have used oxytocin or other uterotonics after birth to avoid medical interventions. 41 There are few studies such as ours that assess perinatal outcomes for women that chose a birth team specifically for their use of the RMC model of assistance. According to a recent systematic review on the topic, it has been recommended that the choice for the active management of the third period be discussed before birth.…”
Section: Discussionmentioning
confidence: 99%
“…40 Our findings indicating that water birth may prevent perineal tears are in line with results from a recently published Swedish study. 41 There are few studies such as ours that assess perinatal outcomes for women that chose a birth team specifically for their use of the RMC model of assistance. 42 We had a very high percentage of answers for the first questionnaire, 70%.…”
Section: Discussionmentioning
confidence: 99%
“…. 최근 미국, 영국, 이탈리아 등 선진 여러 나라에서 수중 출산이 활발히 이루어지고 있으며 수중 진통과 수중 출산의 효과, 수중 출산의 안전성에 관한 연구 결과가 보고 되고 있다 (Davies et al, 2015;Menakaya et al, 2013;Peacock et al, 2018;Poder & Lariviere, 2014;Thöni et al, 2010;Ulfsdottir et al, 2018). 수중 출산의 효과를 검증한 선행연구에 의하면 진통 중 따뜻한 물 속에 들어가 면 몸이 이완되고 진통이 경감되어 스트레스 반응을 극복 할 수 있게 되고 효과적인 자궁수축을 일으킴으로 분만 시 간을 단축한다고 하였다 (Peacock et al, 2018).…”
unclassified